PENINGKATAN KETERAMPILAN MENULIS TEKS DESKRIPSI MENGGUNAKAN MODEL PEMBELAJARAN COOPERATIVE TIPE PICTURE AND PICTURE DI KELAS IV SD NEGERI 34 DAMA GADANG KABUPATEN AGAM - Dwi Aikhe Faradiya; Chandra Chandra; Muhammadi Muhammadi; Yesni Yenti (STKIP Subang, 2025)
This study was motivated by the low level of descriptive writing skills among fourth-grade students at SDN 34 Dama Gadang Elementary School in Agam Regency. The purpose of this study was to describe the improvement in descriptive writing skills using the Picture and Picture Cooperative model in fourth-grade classes at SDN 34 Dama Gadang Elementary School in Agam Regency. This research is a classroom action research (CAR) using qualitative and quantitative approaches. It was conducted in two cycles, namely cycle I was conducted in two meetings and cycle II was conducted in one meeting. Each cycle consisted of four stages, namely planning, implementation, observation, and reflection. The subjects of this study were teachers and students in grade IV of SDN 34 Dama Gadang, Agam Regency, with a total of 18 students. The results of the study show an improvement, as seen from the Teaching Module aspect in cycle I, which obtained an average of 87.5% with a qualification of (B) and cycle II 95.83% with a qualification of very good (SB). The implementation of learning in terms of teachers in cycle I obtained an average of 86.05% with a good (Baik) qualification, and in cycle II it increased to 97% with an excellent (SB) qualification. The student aspect in cycle I had an average of 86.05% with a good (Baik) qualification, and in cycle II it increased to 97% with an excellent (SB) qualification. The results of the assessment of students' writing skills in cycle I obtained an average of 69.5 with a sufficient (C) qualification, and in cycle II it increased to 84.1 with a good (B) qualification. Thus, the Picture and Picture Cooperative model can improve descriptive text writing skills in grade IV of SDN 34 Dama Gadang, Agam Regency.